Creative approaches to Grammar instruction: A literature review - Tamam, Alya Faiqoh (Universitas Ahmad Dahlan, 2024)
Grammar instruction is a fundamental component of English language learning, providing learners with the structural foundation necessary for effective communication. Despite its importance, many students struggle to engage with grammar due to its perceived complexity and abstract rules. This literature review explores the significance of teaching grammar and examines a range of creative strategies designed to enhance learner engagement and comprehension. Emphasis is placed on the role of English teachers in implementing innovative methods—such as games, storytelling, music, art, and digital tools—to facilitate more dynamic and memorable grammar lessons. The reviewed studies indicate that creative grammar instruction not only improves students’ understanding of grammatical concepts but also fosters critical thinking, collaboration, and intrinsic motivation. Additionally, the review highlights the relevance of 21st-century learning trends, including technology integration and paperless classrooms, in shaping effective grammar pedagogy. Finally, it addresses the need for teacher preparedness in adopting modern and imaginative approaches to grammar instruction.